IDOL N342S variant, atherosclerosis progression and cardiovascular disorders in the italian general population - Dhyani, A.; Tibolla, G.; Baragetti, A.; Garlaschelli, K.; Pellegatta, F.; Grigore, L.; Norata, Giuseppe; Catapano, A. (Public Library of Science, 2015)
Inducible degrader of the low density lipoprotein receptor (IDOL), is an E3 ubiquitin ligase that negatively modulates low density lipoprotein receptor (LDL-R) expression. Genome-wide association studies (GWAS) indicated that genetic variants in IDOL gene contributes to variation in LDL-C plasma levels and the detailed analysis of a specific locus resulted in the identification of the functional common single nucleotide polymorphism (SNP) rs9370867 (c. G1025A, p.N342S) associates with increased LDL-R degradation and increased LDL-C levels. These findings, however, were not confirmed in two other independent cohorts and no data about the impact of this variant on atherosclerosis progression and cardiovascular risk are available. Aim of this study was to investigate the association between a functional variant in IDOL and atherosclerosis progression in an Italian general population. 1384 subjects enrolled in the PLIC study (Progression of Lesions in the Intima of Carotid) were genotyped by Q-PCR allelic discrimination and the association with anthropometric parameters, plasma lipids and the carotid intima media thickness (cIMT) and the impact on cardiovascular disease (CVD) incidence were investigated. The N342S variant was not associated with changes of the plasma lipid profile am ong GG, AG or AA carriers, including total cholesterol (249±21, 249±19 and 248±21 mg/dl respectively), LDL-C (158±25, 161±22 and 160±23 mg/dL), cIMT (0.74±0.14, 0.75±0.17 and 0.77±0.15 mm) and CVD incidence. In agreement, the expression of LDLR and the uptake of LDL was similar in macrophages derived from GG and AA carriers. Taken together our findings indicate that the N342S variant does not impact plasma lipid profile and is not associated with atherosclerosis progression and CVD in the general population, suggesting that other variants in the IDOL gene might be functionally linked with cholesterol metabolism.